Overcoming Initial Deficiencies in Confidence and Classroom Management of English Education Students at Teaching Practicum - Nurteteng, Nurteteng; Nursalim, Nursalim; Fergina Lengkoan (English Education Department, 2024)
This study investigates the challenges faced by English Education students at Universitas Pendidikan Muhammadiyah Sorong due to deficiencies in foundational English skills, focusing on their confidence and classroom management during teaching practicums. The research has three primary objectives: to identify specific challenges, analyze the impact of these deficiencies on students' confidence and classroom management abilities, and propose effective interventions. Utilizing a quantitative research design, data were collected from sixth-semester students through structured surveys and self-report questionnaires, which assessed perceived challenges, confidence levels, and classroom management skills. The findings revealed significant difficulties in vocabulary (72%), grammar (65%), pronunciation (58%), listening comprehension (60%), and speaking fluency (70%), compounded by limited exposure to English-speaking environments. A strong correlation was found between low English proficiency and decreased self-confidence, with 68% of respondents feeling unprepared to manage classrooms effectively. To address these challenges, the study proposes targeted interventions, including enhanced language support programs, peer mentoring, simulation activities, regular feedback mechanisms, and workshops on classroom management. These recommendations aim to improve the teaching practicum experience for English Education students, ultimately fostering their professional development and effectiveness as future educators.